Characteristics of the European Platform Regulation: Platform Law and User Protection - Ződi, Zsolt (Public Governance, Administration and Finances Law Review, 2022)
This paper presents the European regulation of platforms. In its first part, it reconstructs the process by which the concept of ‘platform’ in information technology and marketing have evolved and become a legal concept. This emerged from the mid-2010s, first in amendments of sectoral rules and later in sui generis platform rules. The second part of the paper argues that these rules can be interpreted as an emerging separate area of law, the ‘European platform law’. One of the most important ultimate justifying principles and purposes of this legal corpus is the protection of users. This is achieved through a number of tools, some of which are legal transplants from other legal areas (such as consumer protection), while others are sui generis legal rules created specifically for platforms, such as the protection of user accounts or the explainability and transparency of algorithms.